Phytotoxic Activity of p-Cresol, 2-Phenylethanol and 3-Phenyl-1-Propanol, Phenolic Compounds Present in Cistus ladanifer L. - Cristina Tena; Ana del Rosario Santiago; Dolores Osuna; Teresa Sosa (Plants, 2021)
Numerous studies about the leaf exudate of Cistus ladanifer highlight this Mediterranean shrub as an allelopathic species. Despite the very high diversity of secondary metabolites identified in its labdanum, only a few components have been evaluated. p-Cresol, 2-phenylethanol and 3-phenyl-1-propanol are three phenolic components present in the labdanum of C. ladanifer whose role has not been specified to date. The present study, through a static acute toxicity test, analyzed their activity, with respect to Allium cepa and Lactuca sativa. These three separate compounds and the mixture of all of them have a more or less phytotoxic activity depending on the medium, species and concentration tested. When the test is carried out on paper, the three pure allelochemicals and their mixture at 1 mM significantly inhibited the total germination, the germination rate and the development of the Allium cepa and Lactuca sativa seedlings to a lesser extent, but when the test performed in soil, the effects on the size of roots and cotyledons are attenuated. Furthermore, in the two species tested on paper, the joint action of the three compounds at 1 mM shows a significantly greater inhibition of the measured indices than each of the compounds separately.